Are teacher-credentialing programs providing enough training in multiculturalism for pre-service teachers?. Issue 3 (30th August 2019) - Delk, Tricia Denise
Abstract : Purpose: The purpose of this study is to explore how multicultural curriculum and instruction in a teacher-credentialing program prepared pre-service teachers to work with diverse students. Design/methodology/approach: The research method used was a qualitative approach. The research design was a descriptive single embedded case study to interview pre-service teachers who were in their second semester in a teacher-credentialing program at a university on the west coast and pre-service teachers who were in their final semester in the same teacher-credentialing program. Pre-service teachers discussed their disappointment in the program for their lack of training in how to work with culturally diverse students. Findings: The findings from the study will add to the body of knowledge specific to teacher-credentialing programs, curriculum developers and universal design for learning on K-12 education. Research limitations/implications: As schools become more diverse, an important role of teacher-credentialing courses is to train future teachers with the knowledge to assist culturally diverse students. If teachers were multicultural teachers, they would be better prepared to instruct culturally diverse students and could acknowledge sociocultural resources and information that students bring to the classroom. Originality/value: The study is essential because training teachers to instruct culturally diverse students is critical as student demographics become more diverse.